Pengaruh Diskon, Promosi, Dan Kualitas Pelayanan Terhadap Keputusan Pembelian (Studi Kasus Pada Konsumen Pengguna Jasa Foto Bo Production) - Anca Dwiki Cahya; Nur Hajati; Muhammad Ridwan Basalama (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis research was conducted to determine the effect of discounts, promotions and service quality on purchasing decisions on consumers using BO Production photo services. Which is located at Jl. Gajayana alley 1 No.760, Merjosari District, Malang City, East Java. The method used is explanatory research that aims to explain the position of each variable and its influence between one variable with another variable, and the source of the data used is primary data by distributing Likert scale ciliaries to consumers using BO Production photo services. The sample calculation in this study uses the Slovin formula which produces 80 respondents. The results of this study are the variables of discount, promotion and service quality simultaneously influence and service quality partially affect purchasing decisions.Keywords: discounts, promotions, service quality and purchasing decisions